Perceived Impact of Social Media on Filipino Undergraduates’ English Language Learning - Jensine Kay M. Bulnes (Researchparks Publishing, 2022)
The overwhelming dominance of social media has led many researchers to study its impacts on various aspects of life. Aware of this, the researcher specifically investigated the impact of social media on Filipino undergraduates’ English language learning. To do this, the researcher utilized a quantitative approach to analyze the data from 114 undergraduates of Western Mindanao State University. Findings revealed that the most frequently used social media platform is Facebook. Students reported to have used social media more than an hour daily, primarily to communicate with friends. There were both positive and negative impacts of social media on undergraduates’ English language learning which calls for careful utilization in the part of social media users.